In Vitro, In Silico and Ex Vivo Studies of Dihydroartemisinin Derivatives as Antitubercular Agents - Kalani, Komal; Alam, Sarfaraz; Chaturvedi, Vinita; Singh, Shyam; Khan, Feroz; Srivastava, Santosh K. (Current Topics in Medicinal Chemistry, 2019)
Introduction: As a part of our drug discovery program for anti-tubercular agents, dihydroartemisinin (DHA-1) was screened against Mtb H37Rv, which showed moderate anti-tubercular activity (>25.0 μg/mL). These results prompted us to carry out the chemical transformation of DHA-1 into various derivatives and study their antitubercular potential. Materials and Methods: DHA-1 was semi-synthetically converted into four new acyl derivatives (DHA-1A – DHA-1D) and in-vitro evaluated for their anti-tubercular potential against Mycobacterium tuberculosis H37Rv virulent strain. The derivatives, DHA-1C (12-O-(4-nitro) benzoyl; MIC 12.5 μg/mL) and DHA-1D (12-O-chloro acetyl; MIC 3.12μg/mL) showed significant activity against the pathogen. Results: In silico studies of the most active derivative (DHA-1D) showed interaction with ARG448 inhibiting the mycobacterium enzymes. Additionally, it showed no cytotoxicity towards the Vero C1008 cells and Mouse bone marrow derived macrophages. Conclusion: DHA-1D killed 62% intracellular M. tuberculosis in Mouse bone marrow macrophage infection model. To the best of our knowledge, this is the first-ever report on the antitubercular potential of dihydroartemisinin and its derivatives. Since dihydroartemisinin is widely used as an antimalarial drug; these results may be of great help in anti-tubercular drug development from a very common, inexpensive, and non-toxic natural product.
Keywords: Anti-tubercular activity